Gender differences in predictors of health status in patients with COPD - Tanni, Suzana Erico [UNESP] (2010)
Objective: To evaluate the health status (HS) of COPD patients and to identify the main predictors of HS in these patients according to gender. Methods: The study included 90 COPD patients (60 males and 30 females; mean age = 64 ± 9 years) with a wide range of airway obstruction disorders (mean FEV1 = 56 ± 19% of predicted). The men were individually matched to the women by % of predicted FEV1 (ratio: 2:1). The patients were assessed regarding body composition; six-minute walk distance; perception of dyspnea using the Modified Medical Research Council Dyspnea Scale; Saint George's Respiratory Questionnaire (SGRQ); Charlson comorbidity index; and the multidimensional Body mass index, airway Obstruction, Dyspnea, and Exercise capacity (BODE) index. Multiple linear regression analysis was performed to identify the predictors of HS by gender. Results: Impairment of HS was greater among the women than among the men for SGRQ total score and for all SGRQ domains (total: 51 ± 18% vs. 38 ± 19%; p = 0.002; symptoms: 61 ± 22% vs. 42 ± 21%; p < 0.001; activity: 62 ± 18% vs. 49 ± 21%; p = 0.004; and impact: 41 ± 19% vs. 27 ± 18%; p = 0.001). The multiple linear regression showed that age and perception of dyspnea correlated with SGRQ total score for both genders (males, r2 = 0.42; females, r2 = 0.70; p < 0.05). Conclusions: Our results showed an association between gender and HS in COPD patients. Age and dyspnea are determinants of HS in both genders.